Sistem Pemesanan Paket Wisata Berbasis WEB - Malfiro Ulfah, Hasmi; Mulyono, Herry (Jurnal Manajemen Sistem Informasi, 2023)
PT. Romi Tour And Travel is one of the businesses engaged in the tour and travel business whose data management still uses the help of books. So that there are problems, namely slow dissemination of information, the process of booking tour packages that must come to the place, the process of managing booking services which sometimes occurs errors in recording and calculating costs, as well as the process of making reports that take a long time. The solution to the problems that occur is by analyzing and designing a tour package booking information system using the prototype development method and the unified model language system model using usecase diagram, activity diagram, and class diagram. The purpose of this study is to design a web-based tour package booking information system. The results of the system development can display customer data, tour package data, booking data and payment data and produce reports that can be printed according to their needs.